2015
DOI: 10.1037/a0038680
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in identity and mental health outcomes among young sexual minority women.

Abstract: Previous research suggests that sexual minorities are at greater risk for trauma exposure, mental health problems, and substance use. To date, few studies have examined racial/ethnic differences among sexual minorities in relation to health-related behaviors and outcomes. Furthermore, studies of racial/ethnic differences among young adult sexual minority women (SMW) are virtually non-existent. The current study adds to the previous literature by exploring differences in trauma exposure, sexual identity, mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 88 publications
(125 reference statements)
9
59
3
Order By: Relevance
“…A cross-sectional study of sexual assault survivors found that Black women reported greater depression, PTSD, problem drinking, and drug use than White women and that Black sexual minority women fared worse on these outcomes than Black heterosexual women (Sigurvinsdottir & Ullman, 2015). A recent study of young lesbian and bisexual women recruited through social media found that Asian women reported fewer PTSD symptoms than White women, but there were no race group differences for depression and anxiety (Balsam et al, 2015), confirming other past research (Balsam et al, 2010; Balsam, Beadnell & Molina, 2013). However, other studies have uncovered differences in psychological distress and depression (Bostwick, Hughes, & Johnson, 2005; Kim & Fredriksen-Goldsen, 2012).…”
Section: Psychological Recovery From Sexual Victimization Of Sexual Asupporting
confidence: 74%
See 2 more Smart Citations
“…A cross-sectional study of sexual assault survivors found that Black women reported greater depression, PTSD, problem drinking, and drug use than White women and that Black sexual minority women fared worse on these outcomes than Black heterosexual women (Sigurvinsdottir & Ullman, 2015). A recent study of young lesbian and bisexual women recruited through social media found that Asian women reported fewer PTSD symptoms than White women, but there were no race group differences for depression and anxiety (Balsam et al, 2015), confirming other past research (Balsam et al, 2010; Balsam, Beadnell & Molina, 2013). However, other studies have uncovered differences in psychological distress and depression (Bostwick, Hughes, & Johnson, 2005; Kim & Fredriksen-Goldsen, 2012).…”
Section: Psychological Recovery From Sexual Victimization Of Sexual Asupporting
confidence: 74%
“…The risk of sexual violence is elevated for sexual minorities both in childhood and adulthood (Friedman et al, 2011; Hughes, McCabe, Wilsnack, West, & Boyd, 2010; Morris & Balsam, 2003; Roberts, Austin, Corliss, Vandermorris, & Koenen, 2010; Rothman et al, 2011). A recent study of lesbian and bisexual women has even identified sexual minority status as a risk factor for trauma (Balsam et al, 2015). Risk of sexual victimization may therefore be higher among sexual minorities.…”
Section: Sexual Assault Victimization and Recovery Of Sexual Minoritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, research findings suggest higher rates of depression among SMW of color compared to heterosexual women of color (Cochran, Mays, Ortega, Alegria, & Takeuchi, 2007; Matthews, Hughes, Johnson, Razzano, & Cassidy, 2002; Mays, Cochran, & Roeder, 2004). Findings regarding depression among African-American and Latina SMW compared to White SMW are inconsistent (Aranda et al, 2015; Balsam et al, 2015; Jeong, Veldhuis, Aranda, & Hughes, 2016). Given that lower rates of hazardous drinking, drug use, and depression typically found among women of color compared to White women in the general population are not seen consistently among SMW, it seems likely that dynamics of risk and protection may not operate in the same way among SMW (Cochran et al, 2007; Hughes, Wilsnack, & Kantor, 2016; Hughes et al, 2006; Matthews et al, 2014; Mereish & Bradford, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Research on timing of sexual orientation developmental milestones has demonstrated that men generally reach milestones at an earlier age than women (D’Augelli, 2006; Floyd & Bakeman, 2006; Katz-Wise, 2014; Katz-Wise et al, 2016; Rosario et al, 1996; Savin-Williams & Diamond, 2000). Beyond gender differences, there may be variability in the timing of milestones based on other sociodemographic characteristics, such as race/ethnicity (Balsam et al, 2015; Dubé & Savin-Williams, 1999; Parks, Hughes, & Matthews, 2004; Rosario, Schrimshaw, & Hunter, 2004) or sexual minority subgroup (Katz-Wise et al, 2016; Maguen, Floyd, Bakeman, & Armistead, 2002). …”
Section: Introductionmentioning
confidence: 99%